Total Video-Assisted Thoracic Surgery Sleeve Lobectomy: Suture by Both Hands - Liu, Kai; Jin, Chenhua; Tian, Hui; Shen, Weiyu (The Thoracic and Cardiovascular Surgeon Reports, 2013)
Bronchoplastic procedures offer better long-term survival and quality of life with less morbidity and mortality than pneumonectomies. However, minimally invasive sleeve lobectomy is rarely reported, and the procedure requires more skill even for experienced hands. We report a total video-assisted thoracoscopic right upper sleeve lobectomy for a patient with centrally located lung cancer.
Keywords: VATS; sleeve lobectomy; both hands suturing